Analysis of macroscopic and microscopic rotating motions in rotating jets: A direct numerical simulation. (6th May 2015) - Yang, Xingtuan; Gui, Nan; Yan, Jie; Tu, Jiyuan; Jiang, Shengyao
A direct numerical simulation study of the characteristics of macroscopic and microscopic rotating motions in swirling jets confined in a rectangular flow domain is carried out. The different structures of vortex cores for different swirl levels are illustrated. It is found that the vortex cores of low swirl flows are of regular cylindrical-helix patterns, whereas those of the high swirl flows are characterized by the formation of the bubble-type vortex breakdown followed by the radiant processing vortex cores. The results of mean velocity fields show the general procedures of vortex origination. Moreover, the effects of macroscopic and microscopic rotating motions with respect to the mean and fluctuation fields of the swirling flows are evaluated. The microscopic rotating effects, especially the effects with respect to the turbulent fluctuation motion, are increasingly intermittent with the increase in the swirl levels. In contrast, the maximum value of the probability density functions with respect to the macroscopic rotating effects of the fluctuation motion occurs at moderate swirl levels since the macroscopic rotating effects are attenuated by the formation of the bubble vortex breakdown with a region of stagnant fluids at supercritical swirl levels.